The NovelNest / Wan Aisyah Amirah Wan Muhammad Nizam and Afzanizam Muhammad - Wan Muhammad Nizam, Wan Aisyah Amirah; Muhammad, Afzanizam (2024)
Proposing the installation of locally crafted wooden outdoor furniture at the Universiti Teknologi MARA (UiTM) campus in Seri Iskandar aims to enrich the student experience by creating inviting and functional outdoor spaces. Emphasizing sustainability, the project utilizes timber materials that harmonize with the university campus environment. The focus is on enhancing student well-being, fostering interpersonal communication, and promoting academic engagement. Through the integration of ergonomic design principles and attention to campus aesthetics, the proposed furniture offers students versatile and comfortable seating options for studying, learning, and relaxation. By cultivating a sense of community and connection to nature, this initiative strives to elevate the overall campus atmosphere and support student success at UiTM Seri Iskandar. This endeavor aligns with the broader goal of public space design on university campuses, which seeks to cater to the diverse needs of visitors, staff, and students while encouraging social interaction, physical activity, and community involvement. The introduction of sustainable wooden furniture not only enhances the campus environment but also contributes to a sense of belonging and well-being among the campus community, fostering a vibrant and inclusive atmosphere for all.